An Experimental Diachronic Exploration of Patination Methodology of Dark Patinated (Arsenical) Copper Alloys on Case Studies from the Eastern Mediterranean Bronze Age and Early Iron Age - Marianne Talma (EXARC, 2018)
Artificially patinated copper alloys are found archaeologically in polychrome artefacts from the 19th century BC Egypt to historical and contemporary Japan. The unusual colour variations observed in these patinas, ranging from black to blue to purple, is due to a minor amount of gold (Au) and silver (Ag) in their copper matrix, whereas accompanying elements such as tin (Sn), iron (Fe), and arsenic (As) might influence workability, hue or shine. Their patina consists of cuprite (Cu2O) however sometimes it may also contain tenorite (CuO). The process in which artificial patination was achieved in prehistory is unknown, however specialized knowledge exists for the production of the modern Japanese irogane alloys. As part of a master’s thesis project (Talma, 2015), the goal was to explore possible patination agents feasible for the Eastern Mediterranean Bronze Age, and to investigate observations put forward by Giumlia-Mair and Lehr (1998; 2003). Production of 4 arsenical copper alloys and material analysis (ICP-OES, SEM [ICP-OES: Inductively Coupled Plasma – Optical Emission Spectroscopy; SEM: Scanning Electron Microscope.]) was done in laboratories of Deutsches-Bergbau Museum in Bochum (Germany), while 4 arsenic free copper alloys were cast in a goldsmith’s workshop (Birgit Doesborg) in the Netherlands. A polymetallic eutectic was observed in the production of the alloys which raises questions with regard to other experimentally produced samples and production choices in antiquity. Common salt (NaCl) represents one possible patination ingredient to compare with the archaeological material, and corroborates earlier work by other authors. The author is greatly indebted to communication and help from experienced goldsmiths David Loepp (IT), Louis Hankart (NL) and Birgit Doesborg (NL).